Upaya Peningkatan Kualitas Kopi Rakyat Dengan Teknologi Wet Process : (Studi kasus : Dsn Sumbercandik, Desa Panduman, Kec. Jelbuk, Kab. Jember) - Latifa Mirzatika Al-Rosyid; Sawitri Komarayanti (Jurnal Teknik Lingkungan, 2021)
Coffee is one of the smallholder plantation commodities whose productivity development is quite potential and has a major influence on the development of the Jember District, especially the northern part of Jember. This research on coffee quality improvement using wet process technology was conducted at the Sukma Elang coffee farmer group in Sumbercandik, Panduman Village, Jelbuk Sub-district, Jember District. This research is one of the strategies to promote Jember products, especially in the field of coffee plantations as an effort to use environmental management technology in the Sumbercandik coffee plantation area. People's coffee in Jember still needs to be fostered in its cultivation, so the role of appropriate environmental management technology is very much needed. Wet process processing technology is one solution to increase optimal results with better quality. Coffee processing with wet process technology produces coffee beans with better quality and can be done on a small scale (farmer level). The purpose of this study is to improve the quality of the coffee beans produced so as to produce high economic value using wet process environmental management technology. The method used in this research was the collection of primary and secondary data. The harvesting equipment used was done by recording the type of harvesting equipment used in the coffee harvesting process in the garden. Analysis of research data includes testing the physical quality of coffee beans which is carried out referring to SNI No. 01-2907-2008. The results showed that wet process coffee processing technology could improve the physical quality and taste of coffee beans. However, further guidance is still needed on optimizing production through escort and group assistance in producing further coffee.